2019
DOI: 10.1016/j.jsxm.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Transgender Individuals After Gonadectomy and Long-Term Gender-Affirming Hormonal Treatment

Abstract: Introduction Establishing the influence of long-term, gender-affirming hormonal treatment (HT) on bone mineral density (BMD) in transgender individuals is important to improve the therapeutic guidelines for these individuals. Aim To examine the effect of long-term HT and gonadectomy on BMD in transgender individuals. Methods 68 transwomen and 43 transmen trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Cross-sectional studies show that lumbar spine and femur neck BMD after many years of GAHT in transmen are in line with the reference population included in the studies [ Table 2(a) ]. 45 , 65 , 67 According to Dobrolinśka et al , 51 total hip BMD was highest between 10 and 15 years of GAHT and significantly lower after 15 years. This long-term data, even if it resulted from a cross-sectional study, suggest that GAHT has no negative effect on bone.…”
Section: Bone Health In Transmenmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies show that lumbar spine and femur neck BMD after many years of GAHT in transmen are in line with the reference population included in the studies [ Table 2(a) ]. 45 , 65 , 67 According to Dobrolinśka et al , 51 total hip BMD was highest between 10 and 15 years of GAHT and significantly lower after 15 years. This long-term data, even if it resulted from a cross-sectional study, suggest that GAHT has no negative effect on bone.…”
Section: Bone Health In Transmenmentioning
confidence: 99%
“…The prevalence of osteoporosis (according to male reference) is around 20% in transwomen after more than 10 years of GAHT. 45 , 51 , 64 …”
Section: Bone Health In Transwomenmentioning
confidence: 99%
“…Results from cross-sectional studies including trans women on longer-term (> 3 years) GAHT are more equivocal. Some studies showed higher hip and femoral neck aBMD in trans women on long-term GAHT as compared to cis men [15,16], although in general, Z-scores remain normal after up to 12.5 years of GAHT [17][18][19]. In contrast, another study showed lower spine, hip and radius aBMD and lower Z-scores in 23 trans women after 8 years of GAHT as compared to cis men [20], and low bone mass has been described in up to 40% of trans women after long-term GAHT [20][21][22].…”
Section: Trans Womenmentioning
confidence: 99%
“…Zudem sollte eine Knochendichtemessung veranlasst werden, insbesondere bei einer geplan-ten pubertätsunterdrückenden Therapie mittels GnRH-a [3,8]. Vor allem die Anwendung von GnRH-a, aber auch die langjährige Anwendung von CHT kann zu einem Verlust von Knochendichte führen [11,12].…”
Section: Pubertätsarretierung Mittels Gnrh-analogaunclassified